2006
DOI: 10.1007/s10459-006-9002-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Competence: General Ability or Case-specific?

Abstract: Clinical competence, as measured in this study, is based on a combination of specific preclinical knowledge and a problem-solving ability. Case specificity fits perfectly well in this interactional perspective on clinical problem solving but does not explain it. The phenomenon "case specificity" is therefore not solely a result of content knowledge, but of level of experience and level of case difficulty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 34 publications
2
30
0
3
Order By: Relevance
“…Only 2 cases were used in the study which may have resulted in a case specificity effect (ie, an individual's ability to solve problems varies across cases), implying that the results from these 2 cases may not apply to other cases. 22 In addition to the low number of cases used in the study, an unanticipated yet significant case effect was found that impacted the results and highlights the need for using factual evidence when responding to highly sensitive topics and legal/ethical dilemmas.…”
Section: Discussionmentioning
confidence: 91%
“…Only 2 cases were used in the study which may have resulted in a case specificity effect (ie, an individual's ability to solve problems varies across cases), implying that the results from these 2 cases may not apply to other cases. 22 In addition to the low number of cases used in the study, an unanticipated yet significant case effect was found that impacted the results and highlights the need for using factual evidence when responding to highly sensitive topics and legal/ethical dilemmas.…”
Section: Discussionmentioning
confidence: 91%
“…Performance on one medical case does not necessarily predict performance on subsequent cases because case specificity leads to different performance outcomes (Fitzgerald et al, 1994;van der Vleuten & Swanson, 1990;Wimmers et al, 2006). In fact, the correlation between diagnostic performances across cases has been reported as low as 0.1 to 0.3 (Norman, Tugwell, Feighter, Muzzin, & Jacoby, 1985).…”
Section: Related Workmentioning
confidence: 99%
“…Research investigating clinical reasoning has illustrated the importance of case specificity in medical education (Fitzgerald et al, 1994;van der Vleuten & Swanson, 1990;Wimmers, Splinter, Hancock, & Schmidt, 2006); this phenomenon refers to the variability in performance from case to case in medical problem solving. The prior knowledge that is associated with different diseases and their underlying physiological processes, combined with the prevalence of certain diseases, opportunities to encounter them in practice and gather detailed information, means that cases may vary in their level of difficulty.…”
Section: Introductionmentioning
confidence: 99%
“…In a study involving medical students, on ten different clerkships/rotations, structural equation modelling demonstrated that in some contexts nearly 40% of reasoning seemed to relate to general problem solving ability 29 .…”
Section: Generic Reasoning Skillmentioning
confidence: 99%